DEVIANT BEHAVIOR OF STUDENTS IN THE SOCIAL AND PSYCHOLOGICAL ADAPTATION IN HIGHER EDUCATION - Elena Yu. Dvoinikova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the article a phenomenon of lying in the context of deviant behavior in social and psycho-logical adaptation in higher education is considered. A complex approach to the analysis of the causes of deviations in the behavior of students is used. The motives of lying in accordance with the accentuation of character students are investigated. Explore areas such as the impact of neurosis on I-conceptual structures of personality: lie as a self-deception both in the form of an inadequate indicator of self-bias, distort the perception of their own social significance and lies as a means to manipulate the behavior of participants in social interaction. The results of the statistical analysis of indicators such as motivational orientation lies, according to the accentuation of character are listed. The dynamics of changes in the motives of lying according to age students is showed. The causation of complex influence neurotic character changes and accentuation of personality of students and their deviant behavior in the process of social and psychological adaptation in high school is displayed. The specific character of modern conditions of education in the context of the impact on the psycho-emotional sphere of students is analyzed. The causality of the effects of information load of a destructive nature to the general state of mental stability of students and their emo-tional burnout are detected. The burnout syndrome in the context of detection of symptoms is described. The highlights the impact of the effect of burnout students on the general mood of the social group is underlined too. The mechanism of inclusion of mental defense mechanisms with the aim of social and psychological adaptation of the person to restore the psychological comfort in the university is showed. The results of the author's use of techniques to determine the motive of lying in the social in-teraction of students is presented. These studies show the relationship of lying students to lie: the opinions of the possibility of forgiveness of yourself and others against the lies are pre-sented. It is proposed to define a lie as a deviant strategy of social and psychological adapta-tion of students in high school.